Henry Van de Velde Prijzen 2002. : Loopbaan - Jong Talent - Bedrijf - Beste Product. - Valcke, Johan; Luyssaert, Bie; Oosterlinck, Christian; Vranken, Inge (Brussel : VIZO, Dienst Vormgeving, 2002)
Verroken, André ; Vandenhoucke, Sylvie ; Verhaert NV ; Thakker, Salima
boek